2003
DOI: 10.1086/378773
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Non‐Gaussian Initial Conditions on the Structure and Substructure of Cold Dark Matter Halos

Abstract: We study the structure and substructure of halos obtained in N-body simulations for a ÃCDM cosmology with non-Gaussian initial conditions. The initial statistics are lognormal in the gravitational potential field with positive (LN p ) and negative (LN n ) skewness; the sign of the skewness is conserved by the density field, and the power spectrum is the same for all the simulations. Our aim is not to test a given non-Gaussian statistics but to explore the generic effect of positive-and negative-skew statistics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 86 publications
(101 reference statements)
2
43
0
Order By: Relevance
“…As mentioned in , it is possible that this internal structure is different in non‐Gaussian with respect to Gaussian models. For instance, there has been some indication in the literature that the concentration and/or inner logarithmic slope of dark matter haloes in cosmological models with primordial non‐Gaussianity and positive skewness is larger than in the standard ΛCDM cosmology (Avila‐Reese et al 2003). This is intuitively in agreement with the fact that in such models it is easier to have high‐density peaks, which should cross earlier the threshold for collapse, with the corresponding structures having more time to relax and compactify.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in , it is possible that this internal structure is different in non‐Gaussian with respect to Gaussian models. For instance, there has been some indication in the literature that the concentration and/or inner logarithmic slope of dark matter haloes in cosmological models with primordial non‐Gaussianity and positive skewness is larger than in the standard ΛCDM cosmology (Avila‐Reese et al 2003). This is intuitively in agreement with the fact that in such models it is easier to have high‐density peaks, which should cross earlier the threshold for collapse, with the corresponding structures having more time to relax and compactify.…”
Section: Discussionmentioning
confidence: 99%
“…They are expected by Amara & Refregier (2004) to yield constraints at a level similar to those set by current all‐sky CMB maps on very large scales. In addition, both the inner density profiles of large dark matter haloes and the abundance of substructure are sensitive to the sign of the skewness of the primordial gravitational potential field (Avila‐Reese et al 2003). Finally, new measurements of the 2 and n ‐point correlation function of local galaxy clusters of different masses will also set tight constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Note that more speculative topics such as the periodicity noted by Broadhurst et al (1990), the presence of large regions underdense in galaxies (Frith et al 2003) or the high correlation length of very massive X‐ray clusters could also hint at primordial non‐Gaussianity. Note also that scale‐dependent non‐Gaussianity has been advocated by Avelino & Liddle (2004) and Chen et al (2003) as a possible way to reconcile the high optical depth to reionization with realistic efficiencies for the formation of the first stars, and that its possible impact on the inner profiles of dark‐matter haloes has been addressed by Avila‐Reese et al (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Since the concentrations of dark haloes are correlated with their mass assembly histories (Wechsler et al 2002), primordial non‐Gaussianities should have an impact on the halo concentration parameter as well. Indeed, N ‐body simulations done by Avila‐Reese et al (2003) showed that positive (negative) skewness in the initial density field results in larger (smaller) halo concentrations. We crudely include this effect by modifying the linear overdensity in as follows (Matarrese et al 2000): …”
Section: Primordial Non‐gaussianitymentioning
confidence: 99%